2022
DOI: 10.21873/anticanres.15895
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Spheroid Proliferation Is Suppressed by a Novel Low-toxicity Compound, Pyra-Metho-Carnil, in a Context-independent Manner

Abstract: Background/Aim: In a screen of compounds to selectively suppress the growth of cancer spheroids, which contained mutant (mt) KRAS, NPD10621 was discovered and associated derivatives were investigated. Materials and Methods: Spheroid areas from HCT116-derived HKe3 spheroids expressing wild type (wt) KRAS (HKe3-wtKRAS) and mtKRAS (HKe3-mtKRAS) were treated with 12 NPD10621 derivatives and measured in three-dimensional floating (3DF) cultures. Several cancers were treated with NPD1018 (pyra-metho-carnil: PMC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The invasion matrix and FCS were added 3 days later and CD73 siRNA was added again. Cells were cultured in a CO 2 incubator as described previously (31)(32)(33). Photomicrographs of cells were taken using a Biozero BZ-8000 (Keyence, Osaka, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…The invasion matrix and FCS were added 3 days later and CD73 siRNA was added again. Cells were cultured in a CO 2 incubator as described previously (31)(32)(33). Photomicrographs of cells were taken using a Biozero BZ-8000 (Keyence, Osaka, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that angiogenesis is crucial for the formation of malignancies as well as the development of metastasis (1). An important agent in encouraging the formation of new blood vessels in tumors is the vascular endothelial growth factor, usually known by the abbreviation VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…3D floating cell culture. Cells were seeded in 96-well plates with round bottoms and ultralow attachment surfaces (product number 7007; Corning Inc., Corning, NY, USA) and treated with PMC on day 0 as described previously (10,12). RNA-seq.…”
mentioning
confidence: 99%